EVADING LAW OF DIMINISHING RETURNS, A CASE OF HUMAN CAPITAL DEVELOPMENT - Arshed, Dr Noman; Rehman, Dr Hafeez ur; Nazim, Muneeba; Saher, Asma (The journal of contemporary issues in business and government, 2021)
For decades economic growth determinants have been the centre of attention among theoretical and development economists. Theoretical economists have built models of economic growth, while development economists were concerned about how these growth models behave in the long run. Previouslyresources were considered as an engine to growth, but they were prone to diminishing returns. The more recent models emphasized the role of knowledge augmented labor which may defy diminishing returns. For this, human capital is proposed as one of the main ingredients to economic growth as proposed by both neo-classical and new growth models. This studyanalyseswhether there is a precedence of the law of diminishing returns in sixty-six lower-income nations of the world.And determine whether the indicators of human capital index (HCI) can ease this diminishing return. The HCI is developed into four sub-indexes which are Capacity, Deployment, Development and Know-how. We used the robust OLS method to find how therefour sub-index of human capital work in this group of countries. The results show that the convergence hypothesishints atthe law of diminishing returns for sample countries. But by investing in human capital, or one of its sub-components, the intensity of diminishing returns will be eased.